The outcome of patients with surgically treated meningioma in England: 1999–2013. A cancer registry data analysis. (2nd November 2019) - Brodbelt, Andrew R.; Barclay, Matthew E.; Greenberg, David; Williams, Matthew; Jenkinson, Michael D.; Karabatsou, Konstantina
Abstract: Purpose: Meningiomas are the commonest predominantly non-malignant brain tumour in adults. The use of surgery appears to be increasing, and outcomes are thought to be good, but whole nation data for England is scarce. The aim of this report is to examine the epidemiology of patients operated for cranial and spinal meningioma in England, and to assess associations between outcomes and gender, age, meningioma site (cranial or spinal), and grade. Material and methods: A search strategy encompassing all patients coded with cranial and spinal meningioma treated between January 1999 and December 2013 was obtained from data linkage between the National Cancer Registration and Analysis Service and Hospital Episode Statistics for England. Results: 25, 694 patients were diagnosed with meningioma in England between 1999 and 2013, in whom 24, 302 were cranial and 1392 spinal. Of these patients, 14, 229 (60%) cranial and 1188 (85%) spinal meningioma received surgery. Of those operated on 70.1% were women, and, where the tumour grade was recorded, 79.5% were WHO grade I, 18.4% grade II, and 2.1% grade III. Five and ten year net survival rates for surgically treated cranial meningiomas were respectively 90% and 81% for those with WHO grade I, 80% and 63% for grade II, and 30% and 15% for WHO grade III tumours. Overall survival after surgery is better in women, younger adults, and people with spinal or lower grade meningiomas. Outcomes have improved over the time period examined. Conclusion: The outcome for patients with meningioma is good and is improving. However, there remains a significant mortality related to the disease process.